Physiological and biochemical responses of okra seed (Abelmoschus esculentus) to fungicides and containers - KUMAR, SUNIL; JAKHAR, SATBIR SINGH; MALIK, ANIL KUMAR (The Indian Journal of Agricultural Sciences, 2022)
The present study was carried out at Department of Seed Science and Technology, CCS Haryana Agriculture University, Hisar, Haryana during 2018–20, that comprised of seven fungicides used as seed treatment @2 gm/kg, viz. carbendazim, tebuconazole, difeconazole, flusilazole, chlorothalonil, azoxystrobin and vitavax power along with control. The freshly harvested okra seeds treated with these fungicides were stored in three different containers, viz. polythene bag, hermetic bag and metal box under ambient conditions up to a period of 18 months and their quality was assessed at a regular interval for three months. A significant decline in seed quality was observed in all the treatments as the period of ageing increased. Seeds treated with azoxystrobin and stored in metal box recorded significantly higher germination per cent (74.9%), shoot length (8.8 cm), root length (6.8 cm), seedling dry weight (0.230 g), vigour index-I (1171), vigour index-II (17.22), catalase (198.9 mg/protein/min), superoxidase dismustase (132.2 mg/protein/min), dehydrogenase (0.46 OD/g/ml) and peroxidise (676 mg/protein/min) and lower electrical conductivity (1.036 μS/cm/g) after 18 months of storage as compared to control. Hence, the study recommends that use of appropriate packaging material and seed treatment would leads to prolong the longevity and health of okra seeds.